Thermal Instability of an Oldroydian Viscoelastic Fluid in Porous Medium - Sharma, R.C.; Kumar, P. (Engineering Transactions, 1996)
The thermal instability of an Oldroydian viscoelastic fluid in porous medium is considered. Following the linearized stability theory and normal made analysis, the dispersion relation is obtained. For stationary convection, the medium permeability is found to have a destabilizing effect. A sufficient condition for non-existence of overstability is obtained. The thermal instability of a rotating Oldroydian viscolastic fluid in porous medium is also studied wherein the rotation is found to have a stabilizing effect on the stationary convection and the sufficient conditions for non-existence of overstability are obtained.